(untitled) (Academicia Globe: Inderscience Research, 2022)
Representatives of the normal microflora of intestinal biota perform a physiologically important function of maintaining the constancy of the internal environment of the body, take part in the formation of the immunobiological reactivity of the macroorganism. Violation of normocenosis contributes to the chronicity of pathological processes (in particular, atopic dermatitis).